Awareness of restorative dental treatment as shown by nursing students in Ibadan - O. Sulaiman, Amidu; K. Kanmodi, Kehinde (Journal of Stomatology, 2017)
Aim of the study. To determine the level of awareness of nursing students in Ibadan, South Western Nigeria, of restorative dental treatment. Material and methods. Well-structured pre-tested questionnaire was submitted to the three randomly selected schools testing the level of awareness of dental treatment and restorative materials. Results. Of the 302 respondents, almost all (99.0%) were aware of the dental profession, but as many as 77.5% of them had never visited a dentist. The majority (87.4%) were aware of the possibility of replacement of a missing tooth, only 66.2% were aware of the possibility of restoration of a broken tooth, while a little above half (53.6%) were aware of the possibility of restoration of a discoloured tooth. Only 30 respondents (9.9%) believed that a broken tooth can improve facial beauty, five respondents (1.7%) believed that missing teeth can improve facial beauty, while only 42 respondents (13.9%) believed that both broken and missing teeth can improve facial beauty (p– value<0.0001). More than four-fifth of the respondents (84.4%) knew the use of removable dentures, 25.2% knew the use of dental amalgam, 17.2% were aware of a dental bridge, 23.5% knew the use of composite, 27.5% knew the use of dental crown in restorative dentistry. Conclusion. The majority of respondents had never visited a dentist for any routine dental check-up. Many of them have poor knowledge of basic restorative dental treatment; this is a strong indicator that they lack the basic knowledge of clinical dentistry. In order to improve the clinical acumen and versatility of nurses, regular training courses on basic clinical dentistry should be incorporated into the curriculum of all kinds of nursing programs in Ibadan, and even in Nigeria at large. This will help in empowering nurses in educating, and counselling of individuals with oral health problems to seek early and professionallydelivered oral health care. This eventually will go a long way in reducing the prevalence of oral health problems and the complications of delayed dental treatment that is commonly reported in Nigerian population.